Impact of etiology on force and kinetics of left ventricular end-stage failing human myocardium. (July 2021) - Mashali, Mohammed A.; Saad, Nancy S.; Canan, Benjamin D.; Elnakish, Mohammad T.; Milani-Nejad, Nima; Chung, Jae-Hoon; Schultz, Eric J.; Kiduko, Salome A.; Huang, Amanda W.; Hare, Austin N.; Peczkowski, Kyra K.; Fazlollahi, Farbod; et al.
Abstract: Background: Heart failure (HF) is associated with highly significant morbidity, mortality, and health care costs. Despite the significant advances in therapies and prevention, HF remains associated with poor clinical outcomes. Understanding the contractile force and kinetic changes at the level of cardiac muscle during end-stage HF in consideration of underlying etiology would be beneficial in developing targeted therapies that can help improve cardiac performance. Objective: Investigate the impact of the primary etiology of HF (ischemic or non-ischemic) on left ventricular (LV) human myocardium force and kinetics of contraction and relaxation under near-physiological conditions. Methods and results: Contractile and kinetic parameters were assessed in LV intact trabeculae isolated from control non-failing (NF; n = 58) and end-stage failing ischemic (FI; n = 16) and non-ischemic (FNI; n = 38) human myocardium under baseline conditions, length-dependent activation, frequency-dependent activation, and response to the β-adrenergic stimulation. At baseline, there were no significant differences in contractile force between the three groups; however, kinetics were impaired in failing myocardium with significant slowing down of relaxation kinetics in FNI compared to NF myocardium. Length-dependent activation was preserved and virtually identical in all groups. Frequency-dependent activation was clearly seen in NF myocardium (positive force frequency relationship [FFR]), while significantly impaired in both FI and FNI myocardium (negative FFR). Likewise, β-adrenergic regulation of contraction was significantly impaired in both HF groups. Conclusions: End-stage failing myocardium exhibited impaired kinetics under baseline conditions as well as with the three contractile regulatory mechanisms. The pattern of these kinetic impairments in relation to NF myocardium was mainly impacted by etiology with a marked slowing down of kinetics in FNI myocardium. These findings suggest that not only force development, but also kinetics should be considered as a therapeutic target for improving cardiac performance and thus treatment of HF. Graphical abstract: Unlabelled Image Highlights: Impaired baseline contraction/relaxation kinetics is dependent on etiology of HF. Length-dependent activation of force development is not impaired in HF myocardium. Kinetics of HF myocardium do accelerate with heart rate similar to NF myocardium. Isoproterenol has different inotropic action between NF and HF myocardium. Improving impaired contractile kinetics may be key in combating human end-stage HF.